INFLUENCE OF ALLENDE MINERALS ON DEUTERIUM RETENTION OF PRODUCTS OF THE STRECKER SYNTHESIS - Lerner N.R. (My University, 1997)
The α-amino and α-hydroxy acids found in the Murchison carbonaceous chondrite are deuterium enriched. These compounds are thought to have originated from common deuterium enriched carbonyl precursors, by way of a Strecker synthesis which took place in an aqueous solution of HCN, NH3, and carbonyl compounds during the period of aqueous alteration of the meteorite parent body. However, the hydroxy acids found in Murchison are less deuterium enriched than the amino acids. With the objective of determining if the discrepancy in deuterium enrichment between the amino acids and the hydroxy acids found in Murchison is consistent with their formation in a Strecker synthesis, we have measured the deuterium content of α-amino and α-hydroxy acids produced in solutions of deuterated carbonyl compounds, KCN and NH4Cl, and also in mixtures of such solutions and Allende dust at 263°K and 295°K. Retention of the isotopic signature of the starting carbonyl by both α-amino acids and α-hydroxy acids is more dependent upon temperature, concentration, and pH than upon the presence of meteorite dust in the solution. In order to determine if hydroxy acids retain their carbon-bonded hydrons better than amino acids, deuterium exchange of α-hydroxy acids in D2O was investigated at temperatures in excess of 393°K. No measurable exchange of hydrogen was observed. While these results do not rule out the Strecker synthesis as a source of meteoritic amino acids, they do indicate that other reaction schemes may have been more important.